Chevrel's procedure for midline incisional hernia repair-not to be abandoned or forgotten - Nikolovski, Andrej; Cako, Dajana; Argirov, Ivan; Limani, Nimetula; Ulusoy, Cemal (Oxford University Press (OUP), 2024)
The Chevrel technique is a well-established procedure for open repair of midline incisional hernia. This retrospective single-center case series aims to present the outcome of patients with midline incisional hernia treated with a modified Chevrel technique. The modification itself comprehended the use of a single-layer continuous suture for the inverted anterior rectus abdominis muscle sheet for the creation of the "new linea alba" without overlapping. Between January 2017 and December 2023, 40 patients were operated. The overall postoperative morbidity rate was 65%. Hernia recurrence occurred in three patients (7.5%). When the basic principles of the Chevrel technique are respected and conducted, this leads to satisfactory results. The postoperative outcome of this case series showed rates of complications and recurrences in concordance with the already published literature. Therefore, this technique should always be considered for the open approach for midline incisional hernia repair.